IN THE FORMATION OF EDUCATIONAL SKILLS OF FUTURE TEACHERS IMPROVING THE ORGANIZATION OF INDEPENDENT WORK - Koishybekova А.К.; Seitova С.М.; Mazhibaeva Г.П. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article deals with the importance of the types of independent work organized in a math lesson, the ways to increase the creative activity of students, the directions of effective and high-quality math lesson and gives a description of independent work as one of the ways of learning. Independent work, conceived first as an organization of learning and then as a learning process, is crucial for acquiring knowledge and achieving sustainable development, especially on the basis of their formative personality and its transformative concept. The purpose of the study was to identify ways to improve the organization of independent work in mathematical disciplines at the university, its theoretical justification and the development of a methodological system. The author proved their relevance at the present time, in the educational process, indicating the types of work that he uses in practice. Special attention is paid to the personal orientation of the types of independent work. Based on the conducted theoretical research, the article formulates the concept of "pedagogical self-education", substantiates the conclusion that for self-education, a teacher needs to master the basics of information and research activities.